2014
DOI: 10.1523/jneurosci.4701-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Free Bursting in Human Cortex following Hypoxia at Birth

Abstract: The human brain is fragile in the face of oxygen deprivation. Even a brief interruption of metabolic supply at birth challenges an otherwise healthy neonatal cortex, leading to a cascade of homeostatic responses. During recovery from hypoxia, cortical activity exhibits a period of highly irregular electrical fluctuations known as burst suppression. Here we show that these bursts have fractal properties, with power-law scaling of burst sizes across a remarkable 5 orders of magnitude and a scale-free relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 56 publications
5
81
0
Order By: Relevance
“…This is because even though the microscopic dynamics may be inaccessible (e.g., single neurons in humans in vivo, or magnetic domains in ferromagnetic samples), near the critical point their bulk activity yields macroscopic signals that can be detected with EEG (or in the case of Barkhausen noise, a pickup coil). Recently it was shown that human neonatal EEG following hypoxia at birth exhibits bursty activity with lengthy power laws spanning several orders of magnitude (Figure 3a) [44 ]. In this context, size is not a spatial property but rather a measure of the energy released in an event.…”
Section: Scale-free Dynamicsmentioning
confidence: 99%
“…This is because even though the microscopic dynamics may be inaccessible (e.g., single neurons in humans in vivo, or magnetic domains in ferromagnetic samples), near the critical point their bulk activity yields macroscopic signals that can be detected with EEG (or in the case of Barkhausen noise, a pickup coil). Recently it was shown that human neonatal EEG following hypoxia at birth exhibits bursty activity with lengthy power laws spanning several orders of magnitude (Figure 3a) [44 ]. In this context, size is not a spatial property but rather a measure of the energy released in an event.…”
Section: Scale-free Dynamicsmentioning
confidence: 99%
“…Contrasts on EEG analyses were then performed, comparing: i) infants with no IVH, ii) infants with IVH grades 1-2 and iii) IVH grades 3-4. EEG data were exported to MATLAB (Mathworks, Natick, MA, USA), band-pass filtered (0.2-20 Hz), and analyzed using conventional and custom algorithms (Roberts et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Roberts et al 2014;Shew et al 2009). The study of criticality can be dichotomized into two classes: those systems which "self-organize" and those tuned to operate at critical points.…”
Section: Insights From Neurosciencementioning
confidence: 99%
See 1 more Smart Citation
“…Most research has focused on specific patterns: for example, seizure detection and localisation [29,[35][36][37], burst-suppression classification [24,[152][153][154] and detection of the sleep-wake cycle [38]. Classification of a broader variety of EEG background patterns will increase the system complexity.…”
Section: Visual Inspection Of the Eeg Signal Is Routine But Visual Inmentioning
confidence: 99%